Artificial Minds - Franklin Stan (The MIT Press, 1995)
This book combines the best of cognitive science research with artificial intelligence theorizing, building a bridge between areas usually a chasm apart. Preface, Mechanisms of Mind, The Nature of Mind and the Mind-Body Problem, Animal Minds, Symbolic AI, The First AI Debate, Connectionism, The Second AI Debate, Evolution and Natural and Artificial, Artificial Life, Multiplicity of Mind, What Do I Do Now?, What's Out There?, Remembering and Creating, Representation and the Third AI Debate, Into the Future, An Emerging New Paradigm of Mind?, References, Index.